Development and application of a foundational fuel chemistry mechanism for pyrolysis and oxidation of propene and butenes. (15th October 2021) - Liang, Xingyu; Zhu, Shihao; Wang, Xiaohui; Wang, Kun
Highlights: A new foundational fuel chemistry mechanism, TJU mech, was developed. TJU mech described well the molecular weight growth kinetics of C2 -C4 alkanes and alkenes pyrolysis and oxidation. TJU mech incorporated in HyChem model achieved better predictions of for the combustion chemistry of jet fuels. Abstract: Propene and three butene isomers are mediate-sized foundational fuels during the conversion of large hydrocarbons, which play important roles in determining reactivities, combustion properties and emission behaviors of practical fuels. The objective of the present study was to develop a detailed foundational fuel chemistry mechanism to describe the decomposition of propene and three butenes, with emphasis on the molecular weight growth kinetics. In the first part of the paper, a new foundational fuel chemistry mechanism, TJU mechanism or TJU mech, containing 976 species and 11, 505 reactions, was developed based on the CSM master pyrolysis mechanism along with the oxidation reactions stripped from the Aramco Mech 2.0. The thus-developed TJU mech was tested against a comprehensive speciation dataset from the oxidation and pyrolysis of propene and butenes over a wide range of operating conditions. Results showed that TJU mech provided good predictions for fuel conversions, formation of major and minor light products, and molecular weight growth species, including butadiene, cyclopentadiene, cyclohexadiene, benzene, toluene, etc. The second part of the paper involved the applications of TJU mech. Updated with improved understanding of the olefine reaction kinetics, TJU mech was firstly used to describe the formation of molecular weight growth species during pyrolysis of ethane and propane under high conversions, then it was utilized in Hybrid Chemistry model to predict formation of critical intermediates generated from i -octane and two jet fuels, Jet A and JP-10, respectively. Results highlighted importance of foundational fuel chemistry mechanism in describing the combustion kinetics of practical fuels.